Gastrointestinal system-derived secondary gynecologic tumors: 10 years experience at a single center (Annals of Medical Research, 2021)
Aim: To perform a retrospective review of gynecologic malignancies originating from gastrointestinal system (GİS).Material and Methods: The study included 35 patients who underwent surgery at Gaziantep University, Faculty of Medicine, Department of Gynecology and Obstetrics from January 2007 to December 2017 and were diagnosed with secondary gynecological malignancies originating from GİS. The patients’ age, primary tumor, metastatic tumor localization and size were recorded. The malignancies were classified based on origin, as those arising from the colon, appendix, pancreas, stomach, peritoneum, and those of an unknown origin. Results: The mean age of the patients was 50.8 years (min: 24, max: 98) and the mean tumor diameter was 9.8 cm (min: 2 cm, max: 23 cm). Malignancies originating from the colon were most common secondary gynecologic malignancies. The primary tumor was localized at the colon in 21 patients (60%), stomach in eight (22.8%), and in the pancreas in one patient, appendix in one patient, peritoneum in one patient (2.8%). The origin of the primary tumor could not be determined in three patients (8.5%). Of the malignancies originating from the colon (n=21), 16 (76.1%) metastasized to the ovaries, four (19%) to the vagina, one (4.7%) to the cervix, while all tumors originating from the stomach, peritoneum, pancreas, appendix and those derived from the GIS without specific origin metastasized to the ovaries. Of the ovarian metastases, 26 (86.6%) were bilateral while four (13.3%) were unilateral. Conclusion: Female genital system is among the substantial targets of metastasis of GIS-derived tumors. Metastatic tumors have a more aggressive behavior. Metastatic tumors must be distinguished from primary tumors as treatment modalities differ in these tumors. A multidisciplinary approach should be employed in the diagnosis, management and follow-up of cases, and the genital system should be screened carefully during both preoperative assessment and postoperative follow-up in patients with primary GIS malignancies.Keywords: Metastatic Tumor; Gynecologic Tumor; Gastrointestinal System.
Keywords: Metastatic Tumor; Gynecologic Tumor; Gastrointestinal System.